Refractive index change in a double quantum dot structure - Suha Hadi; Mohammed A.A. Abbas; Faten K. Hachim; Baqer Obaid Al-Nashy; Amin H. Al‑Khursan (Results in Optics)
The density matrix theory models the refractive index change in a double quantum dot (DQD) system. The orthogonalized plane wave (OPW) is considered for wetting layer (WL)-quantum dot (QD) transitions, and the transition momenta are calculated. The modeling here considers all possible QD-QD and WL-QD transitions, which is another key property of this work. The results show that the tunneling increment raises the refractive change (RIC) to a huge value. Reducing the probe field enables the superluminal propagation of light, which is of viable importance in optical applications. A weaker probe or a strong pump with moderate tunneling can result in the highest value of RIC.